Brain glycogenolysis, adrenoceptors, pyruvate carboxylase, Na+,K+-ATPase and Marie E. Gibbs' pioneering learning studies - Hertz, Leif; Xu, Junnan; Song, Dan; Du, Ting; Peng, Liang; Yan, Enzhi (Frontiers in Integrative Neuroscience, 2013)
The involvement of glycogenolysis, occurring in astrocytes but not in neurons, in learning is undisputed (Duran et al., JCBFM, in press). According to one school of thought the role of astrocytes for learning is restricted to supply of substrate for neuronal oxidative metabolism. The present ‘perspective’ suggests a more comprehensive and complex role, made possible by lack of glycogen degradation, unless specifically induced by either i) activation of astrocytic receptors, perhaps especially beta-adrenergic, or ii) even small increases in extracellular K+ concentration above its normal resting level. It discusses i) the known importance of glycogenolysis for glutamate formation, requiring pyruvate carboxylation; ii) the established role of K+-stimulated glycogenolysis for K+ uptake in cultured astrocytes, which probably indicates that astrocytes are an integral part of cellular K+ homeostasis in the brain in vivo; and iii) the plausible role of transmitter-induced glycogenolysis, stimulating Na+,K+-ATPase/NKCC1 activity and thereby contributing both to the post-excitatory undershoot in extracellular K+ concentration and the memory-enhancing effect of transmitter-mediated reduction of slow neuronal afterhyperpolarization (sAHP).